2020
DOI: 10.1186/s12951-020-00676-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteins facilitates placental transfer of polystyrene particles

Abstract: Background Nanoparticles, which are exposed to biological fluids are rapidly interacting with proteins and other biomolecules forming a corona. In addition to dimension, charge and material the distinct protein corona influences the interplay of nanoparticles with tissue barriers. In this study we were focused on the impact of in situ formed human plasma protein corona on the transfer of 80 nm polystyrene nanoparticles (PS-particles) across the human placenta. To study materno-to fetal PS transfer we used the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 82 publications
(122 reference statements)
0
46
0
Order By: Relevance
“…This placenta permeability was further confirmed with carbon particles ranging from 1 to 10 µm [ 20 ]. Recently, transplacental movement of nanoplastic particles (<100 nm) has been demonstrated using ex vivo placenta perfusion models [ 6 , 21 , 22 ], which was accompanied by a change in the protein corona composition [ 23 ]. Moreover, the cellular uptake and intracellular accumulation of nano- and microparticles have been shown in placenta in vitro co-culture models [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This placenta permeability was further confirmed with carbon particles ranging from 1 to 10 µm [ 20 ]. Recently, transplacental movement of nanoplastic particles (<100 nm) has been demonstrated using ex vivo placenta perfusion models [ 6 , 21 , 22 ], which was accompanied by a change in the protein corona composition [ 23 ]. Moreover, the cellular uptake and intracellular accumulation of nano- and microparticles have been shown in placenta in vitro co-culture models [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we employed the current gold standard ex vivo placental perfusion model [ 27 ] to assess placental transfer of DEPs towards the fetal circulation in an intact human tissue under physiologically-relevant perfused conditions. Placental perfusion studies were performed for up to 6 h, which has been previously shown to be sufficient to detect placental translocation of various nanoparticles [ 36 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This includes environmental particulates, pathogens and drugs intended for maternal treatment which can have potentially harmful effects on the developing fetus [16]. However, this also offers a potential strategy for targeted therapeutic interventions [44].…”
Section: Exogenous Particlesmentioning
confidence: 99%
“…Endocytosis may also provide a mechanism for targeted placental or fetal therapies. Synthetic nanoparticles in the plasma become coated by serum proteins like albumin and IgG [44]. Serum proteins, and their nanoparticle cargo, may undergo receptor-mediated endocytosis into the syncytiotrophoblast through interactions with endocytic receptors (e.g.…”
Section: Targeted Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation